Enhanced Antibacterial Activity of Dermaseptin through Its Immobilization on Alginate Nanoparticles-Effects of Menthol and Lactic Acid on Its Potentialization - Noura Hazime; Yanath Belguesmia; Alexandre Barras; Mohamed Amiche; Rabah Boukherroub; Djamel Drider (MDPI AG, 2022)
Dermaseptin B2 (DRS-B2) is an antimicrobial peptide secreted by Phyllomedusa bicolor, which is an Amazonian tree frog. Here, we show that the adsorption of DRS-B2 on alginate nanoparticles (Alg NPs) results in a formulation (Alg NPs + DRS-B2) with a remarkable antibacterial activity against Escherichia coli ATCC 8739 and E. coli 184 strains, which are sensitive and resistant, respectively, to colistin. The antibacterial activity, obtained with this new formulation, is higher than that obtained with DRS-B2 alone. Of note, the addition of lactic acid or menthol to this new formulation augments its antibacterial activity against the aforementioned Gram-negative bacilli. The safety of DRS-B2, and also that of the new formulation supplemented or not with a small molecule such as lactic acid or menthol has been proven on the human erythrocytes and the eukaryotic cell line types HT29 (human) and IPEC-1 (animal). Similarly, their stability was determined under the conditions mimicking the gastrointestinal tract with different conditions: pH, temperature, and the presence of digestive enzymes. Based on all the obtained data, we assume that these new formulations are promising and could be suggested, after in vivo approval and completing regulation aspects, as alternatives to antibiotics to fight infections caused by Gram-negative bacilli such as E. coli.